Monitoring of toxicities induced by Chimeric Antigen Receptor T-cell therapy: Protocol for a phenomenological study on the experiences of nurses - Valentina Simonetti; Letizia Governatori; Francesco Galli; Cesare Tozzi; Romano Natalini; Andrea Toccaceli; Francesco Pastore; Giancarlo Cicolini; Dania Comparcini (OPI Napoli, 2024)
Introduction: Chimeric Antigen Receptor T-cell therapy (CAR-T) represents the most recent immunotherapy's innovation to cure some refractory and/or relapsing haematological tumours. However, because of the life-threatening toxicities it might cause such as Cytokine Release Syndrome and Immune Cell Associated Neurotoxicity Syndrome, patients are closely monitored by nurses for the early identification of toxicities during the post-infusion phase of CAR-T cell therapy. Exploring the nurses' experience with respect to any difficulties related to the monitoring is important since these issues can be perceived by patients and affect the nurse-patient's caring relationship, considered as a shared lived experience between the patient and the nurse. Aim: This study aims to investigate haematology nurses' lived experience with monitoring CAR-T's induced toxicities. Materials and methods: A qualitative study following Cohen's phenomenological methodology will be conducted through semi-structured interviews in a sample of Italian nurses working in haematology units, who have had previous experience in the management of patients undergoing CAR-T therapy for at least two months and who have performed the monitoring for the same months of experience; the interviews will be audio-recorded and then transcribed verbatim. Two researchers will carry out the manual analysis and interpretation of the collected data independently, identifying themes and sub-themes. Conclusion: To explore the nurses' experiences in this field could facilitate the identification of the educational needs, at individual and group level. Despite it is important to consider contextual variables, the findings of this study could contribute to develop evidence supporting advanced and specialized nursing care in the haematological setting.